Identifying the influence of pouring temperature, Al-RHA composition, and pattern thickness on the properties of Al-RHA composites produced by evaporative casting - Siswanto, Rudi; Subagyo, Rachmat; Tamjidillah, Mastiadi; Mahmud, Mahmud; Setiawan, Muhammad Soleh Indra (Eastern-European Journal of Enterprise Technologies, 2024)
This study investigated the effect of pouring temperature, Al-RHA composition and pattern thickness on fluidity length, surface roughness at Al-RHA composition (85:15, 80:20, 75:25) %, pouring temperature (650, 700, 750) °C, and pattern thickness (1, 2, 3, 4, 5, 6, 10) mm. The challenge in this study is to optimize the fluidity length and hardness but minimize the surface roughness and porosity of the composite. The results showed that raising the pouring temperature increased the fluidity length, surface roughness, hardness, and porosity. Higher pouring temperature caused an increase in fluidity length by 13.51–54.17 % when the temperature raised from 650 °C to 750 °C. This was accompanied by an increase in hardness by 1.96–10.69 %. However, higher temperature also resulted in increased surface roughness by 3.9–7.92 % and increased porosity by 1.3–3 %. The composition ratio of Al-RHA plays an important role in determining the physical and mechanical properties of the composites. Increasing RHA content tends to increase the fluidity length but increases the surface roughness, hardness, and porosity. The higher RHA content increases the fluidity length by 2.44–11.9 % and the hardness also increases by 1.26–12.87 %. However, the higher RHA composition also increases the surface roughness by 1.2–30.95 % and the porosity increases by 2–2.7 %. The larger pattern thickness increases the fluidity length by 10.53–60.42 %. Controlling the RHA content and pouring temperature is very important to improve the physical-mechanical properties of Al-RHA composites. The results have potential applications in industries that require special composite materials such as automotive, aerospace, machinery and agricultural equipment